Efficiency Enhancement in Job Performance of Civil Defense Volunteers under Supervision of Phunphin District Local Administrative Organization, Surat Thani province - Sadadkhan, Ayab (Journal of Social Development and Management Strategy, 2024)
This article aimed 1) to study factors affecting efficiency enhancement in job performance of Civil Defense Volunteers, 2) to compare the relationship in job performance of Civil Defense Volunteers under supervision of Local Administrative Organization, classified by individual factors, and 3) to study problem status, obstacles, and guidelines for enhancing efficiency in job performance of Civil Defense Volunteers under supervision of Phunphin District Local Administrative Organization, Surat Thani province. A questionnaire was used as a quantitative research instrument. The sample was selected using a purposive sampling or a judgment sampling according to inclusion criteria, including being Civil Defense Volunteers under supervision of Phunphin District Local Administrative Organization, Surat Thani province who passed the trainings at least 3 times. population groups of 190 samples. The study results revealed that most of the participants had a high level of opinions towards factors affecting efficiency enhancement in job performance of Civil Defense Volunteers under Phunphin District Local Administrative Organization, Surat Thani province, the mean was 3.81. Consideration of each aspect found the participants had opinions towards factors affecting efficiency enhancement in job performance of Civil Defense Volunteers in terms of motivation at work the most, followed by knowledge and understanding of the work, building relationship and team work, rewards, and social return, the means were 3.92, 3.89. 3.87 and 3.73